Se definen los frentes : (Agosto 1936) / [redacción Javier Redondo... (et al.)] - Redondo Rodelas, Javier (La guerra civil Española mes a mes ; 4)
Contiene "Semblanzas" de: Álvaro Fernández Burriel, Manuel Goded Llopis, Julio Ruíz de Alda, Juan Yagüe Blanco, Alberto Bayo, Melquíades Álvarez, José María Albiąna